PENDAYAGUNAAN ZAKAT PRODUKTIF DI KAPANEWON SEWON KABUPATEN BANTUL - Risky Eka Amriyanto (Jurnal Riset Daerah, 2024)
Zakat in Indonesia is a huge potential that still needs to be optimized. Moreover, the fact that Indonesia is the country with the largest Muslim population in the world. The strategic position of zakat as a function of a Muslim's social responsibility, if put into practice, can be an alternative for empowering the people. In its development, zakat has been given a regulation through the formation of BAZNAS and its derivatives up to the district level. This research tries to discuss the practice of utilizing zakat in the Kapanewon Sewon, mainly focusing on the relationship between BAZNAS Bantul Regency, UPZ Sewon, Kapanewon Sewon as a regional working unit and mustahik. The data collection method in this research is through observation, interviews and supported by secondary data in the form of supporting documents and documentation. The findings from this research are that there has been a flow of cooperation between zakat managers and the government in distributing productive zakat funds whose presence has been felt by the beneficiaries. However, there are still several aspects that need to be improved, namely related to administration, personnel and the role of implementers in the field. Also no less important are business assistance efforts for mustahik which are still limited.